Environmental, Social and Governance (ESG) disclosure and firm value of manufacturing firms: The moderating role of profitability - Yeye, Olufemi; Egbunike, Chinedu F. (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study examines the impact of environmental, social, and governance disclosure on firm value. This study empirically examines the impact of profitability on the relationship between ESG and firm value. Research methodology: This study uses a panel dataset of 12 industrial goods manufacturing firms listed during the 2014-2020 period. The direct effects were tested using an FEM and the Two-Stage Least Squares was used to account for the endogeneity problem. Results: This study finds a positive effect of ESG disclosures on firm value. The coefficients of ESG in the FEM and 2SLS results were not significant. The interaction between ROA and ESG also showed higher coefficients that were not statistically significant. The empirical analysis was robust to the use of two-stage least squares regression. Limitations: This study presents evidence from a single sector based on a prior literature review, which may affect the generalizability of the findings to other sectors. Contribution: This work adds to the broad ESG literature and methodologically extends past results by exploring the moderating influence of profitability. Practical implications: This study has implications for managers and firms that are increasingly desirous of improving their firm performance by presenting a positive image to their stakeholders and how this is linked to their profitability over time. Novelty: This study adds new aspects to the broad discussion on ESG and firm value in a developing-country context, which is consistent with the view that profitable firms mainly address ESG issues in such economies.